QuantiFERON-TB Gold Plus Assay in Patients With Latent vs. Active Tuberculosis in a Low Incidence Setting: Level of IFN-γ, CD4/CD8 Responses, and Release of IL-2, IP-10, and MIG - Carrère-Kremer, Séverine; Kolia-Diafouka, Pratt; Pisoni, Amandine; Bolloré, Karine; Peries, Marianne; Godreuil, Sylvain; Bourdin, Arnaud; Van de Perre, Philippe; Tuaillon, Edouard (Frontiers in Microbiology, 2022)
Objectives We analyzed the results of the QuantiFERON Glod Plus assay (QFT) and cytokine patterns associated with active tuberculosis (ATB) among patients with positive QFT. Methods A total of 195 patients are QFT-positive, among which 24 had an ATB and 171 had a latent tuberculosis infection (LTBI). Interferon-gamma (IFN-γ) secretion was analyzed relative to interleukin-2 (IL-2), IFN-γ inducible protein or CXCL-10 (IP-10), and monokine induced by IFN-γ or CXCL-9 (MIG) secretion, and then compared between two sets of peptide antigens [tube 1 - cluster of differentiation 4 (CD4+) T cell stimulation; tube 2 - CD4+/CD8+ T cell response]. Results Higher IFN-γ responses were measured in the ATB group (p = 0.0089). The results showed that there was a lower ratio of tube 1/tube 2 IFN-γ concentrations in the ATB group (p = 0.0009), and a median [interquartile ranges (IQR)] difference between the two sets at −0.82 IU/ml (−1.67 to 0.18) vs. −0.07 IU/ml (−0.035 to 0.11, p < 0.0001) in the ATB group compared to the LTBI group, respectively. In addition, patients with low ratios of IL-2/IFN-γ, IP-10/IFN-γ, and MIG/IFN-γ were much more likely to have ATB. Conclusion High levels of IFN-γ secretion, preferential IFN-γ response in tube 2, and lower secretion of IL-2, IP-10, and MIG release relative to IFN-γ secretion were more likely observed in subjects with ATB. These features of T cell response may be helpful in low prevalence settings to suspect ATB in patients tested positive for IFN-γ release assays (IGRA).